2004
DOI: 10.2752/089279304786991945
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards animal use and belief in animal mind

Abstract: Animals are used by humans in many ways, yet science has paid little attention to the study of human-animal relationships (Melson 2002). In the present study participants (n= 96) completed a questionnaire on attitudes towards animal use and individual differences were examined to determine which characteristics might underlie these attitudes ('belief in animal mind', age, gender, experience of animals, vegetarianism, political stance, and living area). It emerged that participants held different views for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
170
4
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 27 publications
(46 reference statements)
18
170
4
6
Order By: Relevance
“…Some recent research has demonstrated that belief in animal mind, belief in animal cognition, and belief in animal sentience is dependent on the species in question (Knight et al 2004;Knight et al 2009), and familiarity with animals improves attitudes and empathy toward them (Wells and Hepper 1995;Fidler, Light and Costall 1996;Cutt et al 2006;Daly and Morton 2009;Morris, Knight and Lesley 2012). Familiarity with animals has previously been demonstrated to influence the attribution of one complex emotion, grief.…”
Section: The Influence Of Owner Demographicsmentioning
confidence: 99%
“…Some recent research has demonstrated that belief in animal mind, belief in animal cognition, and belief in animal sentience is dependent on the species in question (Knight et al 2004;Knight et al 2009), and familiarity with animals improves attitudes and empathy toward them (Wells and Hepper 1995;Fidler, Light and Costall 1996;Cutt et al 2006;Daly and Morton 2009;Morris, Knight and Lesley 2012). Familiarity with animals has previously been demonstrated to influence the attribution of one complex emotion, grief.…”
Section: The Influence Of Owner Demographicsmentioning
confidence: 99%
“…For example, modern dairy farm practices are more accepted by people who opt for the moral value that humans are superior to animals than by people who opt for the moral value that humans and animals are equivalent (Boogaard et al 2011a). Also the moral value that farm animals are being sentient has an influence on the acceptance of animal husbandry practices (Duncan 2006;Knight et al 2004). When a farm animal is considered to be sentient, the effect of animal husbandry practices on pain and/ or distress of the animal has to be justified before the animal husbandry practice can be accepted (Knight et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also the moral value that farm animals are being sentient has an influence on the acceptance of animal husbandry practices (Duncan 2006;Knight et al 2004). When a farm animal is considered to be sentient, the effect of animal husbandry practices on pain and/ or distress of the animal has to be justified before the animal husbandry practice can be accepted (Knight et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…O grau de esforço físico e verbal, expresso pelos manejadores para movimentar bovinos e suínos, é positivamente correlacionado com interações táteis negativas, como tapas, empurrões e batidas (HEMSWORTH & COLEMAN, 1998). Alguns estudos sugerem que existem diferenças entre homens e mulheres na qualidade da interação com animais, com mulheres promovendo uma melhor relação (LENSINK et al, 2000), o que pode ser explicado por diferenças nas atitudes em relação a eles (KNIGHT et al, 2004 é possível melhorar as atitudes e comportamentos dessas pessoas e alcançar, com isso, melhorias na produtividade e bem-estar dos animais.…”
Section: Introductionunclassified